2013
DOI: 10.3390/ma6072578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fracture Width on Sealability in High-Strength and Ultra-Low-Permeability Concrete in Seawater

Abstract: For cementitious composites and materials, the sealing of fractures can occur in water by the precipitation of calcium compounds. In this study, the sealing behavior in a macro-fractured high-strength and ultra-low-permeability concrete (HSULPC) specimen was investigated in simulated seawater using micro-focus X-ray computed tomography (CT). In particular, the influence of fracture width (0.10 and 0.25 mm) on fracture sealing was investigated. Precipitation occurred mainly at the outermost parts of the fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…with a width of 30-50 lm. Let's also note that these healing products display a different appearance than in [18,19]. This difference could be explained by their distinct nature: though a specific study was not conducted, Fukuda et al most likely observed for the most part calcite or portlandite formation (owing to the constant thickness over large zones), while in our study the appearance of local bridges suggests the formation of hydration products (CSH, ettringite or portlandite).…”
Section: Supplements From X-ray Microtomographycontrasting
confidence: 47%
See 1 more Smart Citation
“…with a width of 30-50 lm. Let's also note that these healing products display a different appearance than in [18,19]. This difference could be explained by their distinct nature: though a specific study was not conducted, Fukuda et al most likely observed for the most part calcite or portlandite formation (owing to the constant thickness over large zones), while in our study the appearance of local bridges suggests the formation of hydration products (CSH, ettringite or portlandite).…”
Section: Supplements From X-ray Microtomographycontrasting
confidence: 47%
“…Since this self-healing phenomenon may be more pronounced on the specimen surface and at certain locations rather than others, any techniques capable of quantifying healing products created inside the specimen or yielding global information are to be encouraged. Recently, X-ray computed tomography has been successfully applied [18,19] yet the small voxel size (approx. 20 lm) has until now constituted a considerable limitation, especially when seeking to directly observe hydration-based healing products or small crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Reinhardt and Jooss (2003) showed that fracture sealing is significantly influenced by temperature up to 80 °C, resulting in a decrease in water transport, i.e., more significant sealing with increasing temperature. It 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 has been shown that sealing in engineered cementitious composites in water occurs if the fracture aperture is less than 0.15 mm (Yang et al 2009), while sealing in HSULPC kept in simulated seawater up to 49 days occurred when the fracture aperture was 0.1 mm but not 0.25 mm (Fukuda et al 2012;Fukuda et al 2013). Thus, it seems that not only the composition of cementitious composites and cementitious materials and its spatial distribution but also the surrounding environment affect sealing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…While Heap et al (2013) showed that the water permeability of concrete increases significantly with the progress of fracturing, it is also possible that the sealing of existing fractures and pores affects the permeability of concrete. So far, various reports on the fracture sealing of concrete have been published (e.g., Jacobsen and Sellevold 1996;Hearn and Morley 1997;Hearn 1997;Edvardsen 1999;Reinhardt and Jooss 2003;Granger et al 2007; Van der Zwaag 2007;Homma et al 2009;Qian et al 2009;Yang et al 2009;Ahn and Kishi 2010;Wu et al 2012;Fukuda et al 2012;Fukuda et al 2013). Among this literature, Edvardsen (1999) showed that the sealing of a fracture occurs by the precipitation of calcium carbonate, generated from CO 3 2− in the water and Ca 2+ in the cement paste, and that the fracture aperture and applied water pressure significantly affect the sealing, while the types of cement and aggregate and the hardness of the water have no influence on the sealing rate.…”
Section: Introductionmentioning
confidence: 99%
“…The results found by the latter researchers corresponded with other nondestructive tests used in that research, which were nonlinear modulation of ultrasonic coda waves and 3D microscopy. Precipitation upon healing of construction materials in seawater or in fly‐ash systems can be studied as well . In the latter studies, crystal precipitation is clearly seen after performing repeated X‐ray radiography scanning before and after healing.…”
Section: Healing Efficiencymentioning
confidence: 99%